Projekt międzynarodowy „Digitally Improving Social and Emotional Skills of Primary School Teachers (DigiSEL)” dla nauczycieli edukacji wczesnoszkolnej - Agnieszka M. Barwicka (Problemy Wczesnej Edukacji)
The problems of the 21st century contributed to the creation of the project in cooperation with Italians, Spaniards, Turks, Croats and Poles. The Erasmus+ international project “Digitally Improving Social and Emotional Skills of Primary School Teachers (DigiSEL)” offers digital training and online teaching methods for primary school teachers in Europe with a focus on SEL. With a new generation of students growing up fast and learning differently from others, teachers need to digitally educate themselves to meet their needs and engage their attention in class and e-classes. The project was created to support teachers in building e-relationships using ICT. The author collected information about the project and pointed out practical solutions in social-emotional learning.